Characterization of avian pathogenic Escherichia coli isolated from free-range helmeted guineafowl - Borzi, Mariana Monezi [UNESP]; Cardozo, Marita Vedovelli [UNESP]; Oliveira, Elisabete Schirato de [UNESP]; Pollo, Andressa de Souza [UNESP]; Guastalli, Elisabete Aparecida Lopes; Santos, Luis Fernando dos; Ávila, Fernando Antonio de [UNESP] (Springer Nature, 2018)
Avian pathogenic Escherichia coli (APEC) isolates from apparently healthy free range helmeted guineafowl were characterized. Most of them had a high frequency of virulence associated genes, multi drug resistance and high pathogenicity. We demonstrated that helmeted guineafowl have potential to transmit antibiotic resistant APEC to other species including humans.
Keywords: APEC; Colibacillosis; Numida meleagris; Virulence factors; Zoonotic potential